Social Support Models for Elderly’s Well-Being in Kanchanaburi Province - Salathong, Phackaphon; Thoranee, Rawiwan (Rajapark Journal, 2022)
The objective of this research was to study and analyze social support, including the search for social support models for the elderly’s well-being. It was qualitative research that collected data from in-depth individual interviews, group discussions, field observations, and notes, and used content-based data analysis and interpretation of the phenomena that occurred. The results revealed that: social support for the elderly’s well-being was based on (1) self-level or self-reliance that was an attempt to help themselves as much as possible, to make themselves feel valued; (2) family level was the closeness with the elderly, who played an important role in problem-solving of physical, mental, and social; and (3) community level was the cooperation of groups of people involved in the implementation of care and support for happiness creation that was consistent with family and community problems. There were 3 characteristics of social support models for the elderly’s well-being: (1) a family characteristic was the closeness of all family members. Love, gratitude, and cooperation were essential; (2) the nature of the community was one of cooperation and coordination of the benefits of both the family and community stakeholders; and (3) a key feature of social networks was the collaboration of 3 large groups: health, social service, and local community. These provided care and social support at the family, area, and provincial levels.